Can vocational interests of students be used to recruit suitable candidates for teacher training programmes in technical vocational education and training in Germany? - Hommel, Mandy (Education & training (London), 2024)
PurposeIn Germany, various approaches have been taken to tackle the current teacher shortage in technical and vocational education and training (TVET). One attempt to remedy the shortage in Bavaria has been the introduction of an engineering education study programme at universities of applied sciences. Ideal candidates for this programme should have an interest in both engineering and social interaction. For effective recruitment, therefore, it is necessary to know applicants’ characteristics such as their vocational interests. In this study, the vocational interest profiles of students in TVET teacher training programmes were identified and their interest profiles and further characteristics were compared with those of other VET students at universities and universities of applied sciences.Design/methodology/approachAn online questionnaire based on Holland’s interest theory and adapted from the Allgemeiner-Interessen-Struktur-Test-3 (interest structure test) was administered to 85 students in TVET teacher training programmes at universities and universities of applied sciences in Bavaria. Items regarding reasons for choosing a particular study programme, university location and other personal details were added.FindingsThe vocational interest profiles of students at universities and universities of applied sciences can be described as similar but weakly differentiated. Insights are provided by the characteristics of students such as the majority being first-time academics in the family. The reasons for choosing the degree programme and university location highlight the fact that a large proportion of students in engineering education would not have chosen a teaching-related degree programme if it had not been offered at the respective university of applied sciences.Research limitations/implicationsAlthough the sample in this study was small and, therefore, limiting, it represented a high proportion of TVET teacher training students in Bavaria and a substantial proportion of first-year students in TVET teacher training programmes at universities and universities of applied sciences in Bavaria (section 2.2 and 3.1). Thus, the findings provide valuable insights into commonalities in interest profiles between engineering education students at universities of applied sciences and other TVET students at universities. With respect to the domain of the chosen vocational specialisation, differentiated profiles emerged that, for example, showed a stronger artistic orientation among students in construction technology/wood. For further analysis, the previous variable-centred orientation of the analysis can be supplemented by person-centred analyses (e.g. cluster analysis and latent variable mixture modelling, LVMM) (cf. Leon et al., 2021).Practical implicationsThe findings in this study reveal the potential for attracting candidates to universities of applied sciences if they prefer to study in rather rural areas close to their hometowns. With the aim to educate prospective teachers for future work not only in metropolitan regions but in rural areas too, offering bachelor degree programmes in rural areas would seem promising. A regional option can boost the recruitment of new students and attract candidates that otherwise would be unable to pursue studies or a career as a teacher in vocational education. The results of this study and those of previous studies suggest that universities of applied sciences can cooperate with universities to help solve the teacher shortage problem.Social implicationsOverall, it is apparent that the students' interests reached comparatively high values in all interest orientations and thus are only weakly differentiated. If undifferentiated profiles indicate low levels of career readiness, this significantly affects the recruitment of young people for the teaching profession. Assessing career orientation and promoting vocational interests should be prioritised during secondary school education. Vocational orientation measures are essential and should provide insight into typical activities of daily work life in different professions and thus pique and foster interests.Originality/valueThis study provides insight into how to respond to the teacher shortage in VET by identifying important characteristics of engineering education students using vocational interest profiling.